2024
DOI: 10.1039/d3cp05320b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface chemistry on the mechanochemical decomposition of tricresyl phosphate

Egheosa Ogbomo,
Fakhrul H. Bhuiyan,
Carlos Ayestarán Latorre
et al.

Abstract: Surface chemistry influences the mechanochemical decomposition of antiwear additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…However, Khajeh et al 20 found the reactivity of TCP molecules trended as Fe 3 O 4 < Fe < Fe 2 O 3 by surface chemistry simulations and experiments. Recently, Ogbomo et al 25 found that the reactivity of TCP molecules trended as Fe 3 O 4 ⟨100⟩ < Fe 3 C⟨010⟩ ∼ a-Fe⟨110⟩ by tribochemistry simulations and the rate of decomposition of TCP molecules on all surfaces increased exponentially with temperature and shear stress. Moreover, the presence of base oil molecules lowered the rate constant for TCP molecules decomposition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, Khajeh et al 20 found the reactivity of TCP molecules trended as Fe 3 O 4 < Fe < Fe 2 O 3 by surface chemistry simulations and experiments. Recently, Ogbomo et al 25 found that the reactivity of TCP molecules trended as Fe 3 O 4 ⟨100⟩ < Fe 3 C⟨010⟩ ∼ a-Fe⟨110⟩ by tribochemistry simulations and the rate of decomposition of TCP molecules on all surfaces increased exponentially with temperature and shear stress. Moreover, the presence of base oil molecules lowered the rate constant for TCP molecules decomposition.…”
Section: ■ Introductionmentioning
confidence: 99%